2019
DOI: 10.1177/0300060519862057
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential core genes in Kawasaki disease using bioinformatics analysis

Abstract: Objective The present study aimed to elucidate the underlying pathogenesis of Kawasaki disease (KD) and to identify potential biomarkers for KD. Methods Gene expression profiles for the GSE68004 dataset were downloaded from the Gene Expression Omnibus database. The pathways and functional annotations of differentially expressed genes (DEGs) in KD were examined by Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses using the Database for Annotation, Visualization and Integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…ITGAM , also known as CD11b , belongs to the integrin family and is involved in the regulation of neutrophils, monocyte activation, adhesion, and migration to damaged endothelium associated extracellular matrix. Moreover, studies have shown increased ITGAM levels in peripheral blood and upregulated protein expression in patients with KD ( Reindel et al, 2013 ; Wu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ITGAM , also known as CD11b , belongs to the integrin family and is involved in the regulation of neutrophils, monocyte activation, adhesion, and migration to damaged endothelium associated extracellular matrix. Moreover, studies have shown increased ITGAM levels in peripheral blood and upregulated protein expression in patients with KD ( Reindel et al, 2013 ; Wu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was validated in the mice model by Lau et al (2008) . Studies have shown that serum levels of MMP-9 are elevated in KD patients and were found to play an important role in the development of CAAs ( Takeshita et al, 2001 ; Chua et al, 2003 ; Gavin et al, 2003 ; Wu et al, 2019 ). Perforin-1 ( PRF1 ) is one of the major cytolytic proteins of cytolytic granules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these treatments, the role of gene alteration in the pathogenesis of KD remains to be elucidated. Recently, microarray technology coupled with bioinformatics tools has been used to identify the novel genes associated with the pathogenesis, diagnosis and treatment of KD (Wu et al, 2019;Yazdan et al, 2020). Herein, we have used mRNA expression profile data of GSE18606 to identify hub genes in whole blood that are associated with acute KD.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies found novel immunobiological pathways involved in KD and allowed to identify potential therapeutic targets for KD, they are listed in Table 3 (15,37,(136)(137)(138)(139)(140)(141)(142)(143)(144)(145)(146)(147). Literature data indicate that researchers focused especially on JAK / STAT pathway in the context of vasculitis, thus it could be regarded as a most promising potential target.…”
Section: Potential Therapeutic Targetmentioning
confidence: 99%